2014
DOI: 10.1177/2322093714549107
|View full text |Cite
|
Sign up to set email alerts
|

International Careers and Career Success of Indian Women in Science and Technology: The Importance of Career Capital and Organizational Capital

Abstract: This article presents a study on international careers and career success of Indian women in Science & Technology (S&T). We conducted interviews with 30 (upper) middle class Indian women in New Delhi and Bangalore (India) who pursued careers abroad as self-initiated expatriates (SIEs). Important elements of career capital competencies in international career pursuits and career success of Indian women SIEs in S&T were: (a) families who value higher education and careers of their female children, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…The first theme, having support, revealed that gaining support both at home and at work is a strong need to access participants’ career goals. This is consistent with the findings of Valk et al (2014) that one of the important factors in the success of Indian women in science and technology careers has been the support of their families. Furthermore, Marcinkus et al (2007) found that women who receive more social support can create a better work–life balance and better work outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…The first theme, having support, revealed that gaining support both at home and at work is a strong need to access participants’ career goals. This is consistent with the findings of Valk et al (2014) that one of the important factors in the success of Indian women in science and technology careers has been the support of their families. Furthermore, Marcinkus et al (2007) found that women who receive more social support can create a better work–life balance and better work outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…It would be insightful to analyze family systems and the respective support provided by the nuclear family, the extended family, and friends during periods of movement in greater detail, helping especially women to succeed in international careers and have a family life (cf. Litwak, 1960;Roos, 2013;Valk et al, 2014). Ideally, employers and families would find new ways to create an environment where mobility does not negatively affect family and personal life, and therefore does not reduce individual well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the interpersonal dimension gained further attention (6.8%). Various studies investigated the individual dimensions: subjective and self- reported such as CCA (Webb and Wright, 1996;Cao et al, 2013), satisfaction, whether life, self, career, or job (Gabel et al, 2005;Canhilal et al, 2015), success, whether in the career, job or in self-development (Cerdin and Le Pargneux, 2009;Bashir et al, 2021), the expatriate's perspective on work-family balance (Valk et al, 2014), job security, personal growth, authenticity and ability to live contentedly (Valk, 2021). Other dimensions investigated were knowledge gain (Bonache and Z arraga-Oberty, 2008), financial gains (earnings, salaries) and promotions and the duration to obtain the latter after the assignment (Bolino, 2007).…”
Section: Identifying the Dimensions And Antecedents Of Expatriate Suc...mentioning
confidence: 99%
“…Lastly, the interpersonal dimensions are concerned with relationship building and identification with the team abroad (Harrison and Shaffer, 2005), knowledge transfer among host-country nationals and their career capital gain (Toh et al, 2012), contribution to society What does expatriate success mean? and family (Valk et al, 2014) and work-family balance (from the family's perspective) (Kempen et al, 2015).…”
Section: Identifying the Dimensions And Antecedents Of Expatriate Suc...mentioning
confidence: 99%